2021
DOI: 10.2147/copd.s317118
|View full text |Cite
|
Sign up to set email alerts
|

National Epidemiological Case–Control Study of Pharmacological Smoking Cessation Treatment in Danish Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a progressive lung disease that is mainly caused by smoking, and most patients with COPD are either former or current smokers. The optimal way to slow down disease progression and reduce overall mortality is for patients to stop smoking. Patients with COPD are known to have lower socio-economic status and to be more nicotine-dependent than most other smokers and therefore face difficulties when attempting to quit smoking. Pharmacological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…In a previous publication we addressed the pharmacological smoking cessation in patients with COPD of all ages, but in our present study we included only patients with early onset COPD, since there is a big knowledge gap regarding the treatment of this particular group of patients. In accordance with a previous study on all Danish patients with COPD, we found a higher likelihood among patients with COPD to redeem prescriptions for smoking cessation medication than among their matched controls 39 . We found that cases had an inferior social situation compared to controls.…”
Section: Discussionsupporting
confidence: 92%
“…In a previous publication we addressed the pharmacological smoking cessation in patients with COPD of all ages, but in our present study we included only patients with early onset COPD, since there is a big knowledge gap regarding the treatment of this particular group of patients. In accordance with a previous study on all Danish patients with COPD, we found a higher likelihood among patients with COPD to redeem prescriptions for smoking cessation medication than among their matched controls 39 . We found that cases had an inferior social situation compared to controls.…”
Section: Discussionsupporting
confidence: 92%